The Influence of Islamic Work Ethics and OCBIP on Knowledge Sharing Among Muslim Employees - Hizriah Islami; Fuad Mas'ud (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2020)
Knowledge sharing behavior and organizational citizenship behavior (OCB) plays a major role in organizational development. This study aims to determine empirically the influence of Islamic Work Ethics on Knowledge Sharing with OCBIP (Organizational Citizenship Behavior From Islamic Perspective) as a Moderation Variable. The population in this study were all Muslim employees in Indonesia who were drawn randomly. The samples collected were 100 respondents using purposive sampling technique. The questionnaire was tested first by using the feasibility test of the instrument in the form of validity and reliability tests. The analytical method of this study uses Moderated Regression Analysis (MRA) with the SPSS 24 program which previously passed the classical assumption test. The results of the regression moderation analysis in this study indicate that Islamic work ethics has a positive and significant effect on knowledge sharing of Muslim employees in Indonesia. This study also concludes that OCBIP can moderate the relationship between Islamic work ethics and knowledge sharing among Muslim employees in Indonesia, where the OCBIP variable is called a quasi variable which can also be used as an independent variable.Keywords: OCBIP, Islamic Work Ethics, Knowledge Sharing